Case Report: Common variable immunodeficiency phenotype and granulomatous-lymphocytic interstitial lung disease with a novel SOCS1 variant - María Soledad Caldirola; María Soledad Caldirola; Espantoso Daiana; Andrea Cecilia Gomez Raccio; Ana Luz García; Agustin Bernacchia; Martín Medín; Maria Isabel Gaillard; Daniela Di Giovanni (Frontiers Media S.A., 2024)
Common variable immunodeficiency is a heterogeneous symptomatic group of inborn errors of immunity that mainly affects antibodies production and/or function, predisposing patients to recurrent and severe infections. More than half of them usually develop autoimmunity, lymphoproliferation, enteropathy, and malignancies. Among these conditions, chronic lung disease such as granulomatous-lymphocytic interstitial lung disease is one of the leading causes of death in these patients. Recently, many genes that play a key role in B and T cells' development, maintenance, and/or cytokines signaling pathways have been implicated in the pathogenesis of the disease. Here, we describe the first Argentinian patient presenting with common variable immunodeficiency and granulomatous-lymphocytic interstitial lung disease, harboring two in cis heterozygous variants in the SOCS1 gene.